Women in cottage industry development project in Sarawak, Malaysia : understanding of participation and reasons for leaving the programme - Hassan, Munirah; Md. Sail , Rahim; Ismail, Maimunah; Idris, Khairuddin (EuroJournals, 2008)

(untitled)
The purpose of this study was to explore the participation of rural women in the group based approach of the Cottage Industry Development Programme (CIDP) of the Ministry of Agriculture, Sarawak in Malaysia. The participants of the study comprised members of the CIDP from the villages of Sejingkat, Buntal, Telaga Air and Selang Ulu located in Kuching District. Seventeen participants were purposefully selected and interviewed. Guided by questions and constant comparative method, the findings revealed that participants joined the programme because of (i) the need to make up the number to be eligible for the programme; (ii) deference to the senior members, and (iii) their interest in business and programme activity. The findings also revealed that none of the participants was involved in the formulation of the CIDP. Formulation of the CIDP was top-down rather than participative and participants were passive recipients rather than seen as partners. Finally, the findings revealed that participants left the programme due to lack of incentives, absence of responsible leadership, lack of disciplines among members and unfulfilled promises by development agents